Sub-Saharan Africa : HIV / AIDS on University Campuses - Kelly, M.J. (2012)
The failure of many African universities to speak out and confront the HIV/AIDS crisis head-on leads to the unraveling of hard-won development gains and crippling prospects for future economic growth. The report, "Challenging the Challenger: Understanding and Expanding the Response of Universities in Africa to HIV/AIDS," based on seven case studies (Benin, Ghana, Kenya, Namibia, South Africa, and Zambia), seeks to understand how the disease is affecting African universities and to identify responses and coping mechanisms that might profitably be shared with sister institutions in similar circumstances. The studies show that HIV/AIDS is having a serious impact on the fiscal situation of the universities in much the same ways as it does on other institutions. The disease increases operating costs, reduces productivity, diverts resources, and threatens sources of income. The case studies insist that committed leadership among the university's top management is the foremost requirement to combat this crisis.